Different Linear and Angular Craniometric Parameters of Posterior Cranial Fossa and Foramen Magnum Based on Reconstructed Computed Tomography Images - Yadav, Vikrant; Prasad, Ravi Shankar; Sahu, Anurag; Mishra, Manish Kumar; Pradhan, Ravi Shekhar (Medical Research and Its Applications Vol. 10, 2024)
Background: The posterior cranial fossa (PCF) and the foramen magnum (FM) are the critical anatomical components of the craniovertebral junction region, which comprise and transmit numerous vital neurovascular structures. So, a fundamental knowledge of the basic radiological anatomy of PCF and FM is of paramount importance in the evaluation of associated pathologies and approaching these areas surgically. The craniometric dimensions of PCF and FM may differ in various regions of India. Aim: The aim of this study is to describe different linear and angular craniometric parameters of PCF, FM and surrounding territory based on reconstructed computed tomography (CT) images. Materials and Methods: This study was conducted in our tertiary care hospital in northern India from the period of January 2023 to June 2023 on 120 patients, and CT screening was done for the head and spine region following a history of head injury. Patient information was anonymized and de-identified prior to analysis. Demographical descriptions and radiological were recorded for all patients included in this study. Results: In this study, 120 patients were included, of whom 50.83% (n = 61) were females and 49.17% (n = 59) were males. Age ranged from 18 to 70 years with a mean age of 43.5 ± 14.08 years. The mean values for linear craniometric parameters of PCF were statistically nonsignificant for different age groups. Statistically significant differences were found for twinning line (TL) (p < 0.0001), McRae’s line (< 0.0001), clivus length (< p < 0.0001), internal occipital protuberance-opisthion line (p = 0.01), Klaus’ index (p < 0.0001), height of posterior fossa (h) (p < 0.0001), h/TL (p = 0.028), when these values were compared for the genders. The measurements of FM transverse diameter, anteroposterior diameter and area were 27.12 ± 1.42 mm (range 23.6–30.1 mm), 30.99 ± 2.23 mm (range 27.6–35.8 mm) and 691.32 ± 30.35 mm2 (range 632.7–777.7 mm2). The values of clivus canal angle (p = 0.038) and clivo-odontoid angle (p = 0.012) were statistically significant when compared for different age groups. The values of Boogard’s angle (p = 0.021) and tentorial slope (p = 0.031) were statistically significant when these were compared for the genders. The evolution of imaging modalities has increased the precision of our knowledge regarding PCF and FM. We used easily available reconstructed CT images to analyse the morphometry of PCF and FM. Conclusions: This study described almost all the linear and angular craniometric parameters used in the morphometric analysis of PCF and FM. The findings of this study provide valuable data regarding linear and angular craniometric parameters of PCF and FM which can redefine reference values.